ChemInform Abstract: Towards Realistic Surface Science Models of Heterogeneous Catalysts: Influence of Support Hydroxylation and Catalyst Preparation Method. Issue 25 (3rd June 2013) - Sterrer, Martin; Freund, Hans‐Joachim
Abstract Review: 103 refs.